2014
DOI: 10.1021/ma501014u
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Depletion and Electrostatic Interactions in Polyelectrolyte–Nanoparticle Systems

Abstract: We use a numerical implementation of polymer self-consistent field theory to study the effective interactions between two spherical particles in polyelectrolyte solutions. We consider a model in which the particles possess fixed charge density and the polymers contain a prespecified amount of dissociated charges. We quantify the polymer-mediated interactions between the particles as a function of the particle charge, polymer concentrations and particle sizes. We study the interplay between depletion interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 102 publications
2
57
0
Order By: Relevance
“…The subtle behavior of such systems is fully dependent on the structural properties of biomacromolecules such as charge, contour length, monomer distribution or degree of ionization. 34 Moreover, the surface curvature and chain persistence length also influence the adsorption process as studied by Kampmann et al for semi-flexible polymers. The stabilization and association behavior can also be regulated by adjusting the solution properties.…”
Section: Introductionmentioning
confidence: 99%
“…The subtle behavior of such systems is fully dependent on the structural properties of biomacromolecules such as charge, contour length, monomer distribution or degree of ionization. 34 Moreover, the surface curvature and chain persistence length also influence the adsorption process as studied by Kampmann et al for semi-flexible polymers. The stabilization and association behavior can also be regulated by adjusting the solution properties.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of oscillatory interactions is also reported in other PE solutions . Pryamitsyn and Ganesan studied the effective interaction between two spherical charged particles in a PE solution with Θ solvent. They reported that for weakly charged particles, the effective interaction is dominated by a depletion‐like short‐range attraction and a long‐range electrostatic Debye–Hückel‐like repulsion, while for some parametric regime, a weaker but longer range bridging attraction appears.…”
Section: Introductionmentioning
confidence: 62%
“…Here ω 0 is a constant, which is large enough to ensure the impenetrability of ions into the particle core. Other choices for ωex(r) are also possible …”
Section: Theory and Modelmentioning
confidence: 99%
See 2 more Smart Citations